Lung ultrasound in children, WFUMB review paper (part 2) - Dietrich, Christoph F.; Buda, Natalia; Ciuca, Ioana Mihaiela; Dong, Yi; Fang, Cheng; Feldkamp, Axel; Jüngert, Jörg M.; Kosiak, Wojciech; Mentzel, Hans Joachim; Pienar, Corina; Rabat, Jorge S.; Rafailidis, Vasileios; et al. (Medical Ultrasonography, 2021)
Ultrasound (US) is an ideal diagnostic tool for paediatric patients owning to its high spatial and temporal resolution, realtime imaging, and lack of ionizing radiation and bedside availability. In the current World Federation of Societies for Ultrasound in Medicine and Biology (WFUMB) paper series so far (part I) the topic has been introduced and the technical requirements explained. In the present paper the use of US in the lung in paediatric patients is analysed. Lung diseases including the interstitial syndrome, bacterial pneumonia and viral infections, CoViD findings, atelectasis, lung consolidation, bronchiolitis and congenital diseases of the respiratory system including congenital pulmonary airway malformation (CPAM) and sequester but also pneumothorax are discussed.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Atelectasis; CoViD; Guidelines; Pneumonia; Pneumothorax